Comparative Study of Acetylation of Alcohols and Phenols with Different Acetylating Agents Using Zinc Chloride as Catalyst Under Solvent Free Conditions at Room Temperature - Yadav, Prakrati; Lagarkha, Rekha; Ahmad Balla, Zahoor (Asian Journal of Chemistry, 2010)
Efficient acetylation of 1º, 2º and 3º, benzylic alcohols and phenols under solvent free conditions at room temperature in presence of less toxic, easily available and in-expensive catalyst ZnCl2, using acetic anhydride or acetyl chloride as an acetylating agent. On comparative study of these two acetylating agents, the acetyl chloride seemed to be better acetylating agent.